Early Childhood Learning Based on Local Wisdom of The Banyumas Region in Early Childhood Education Institutions in RA Masyithoh 13 Sokaraja Lor - Fajarini , Asniar; Wachid Bambang Suharto, Abdul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Early childhood education is the foundation for creating a generation of character and quality. Early childhood education based on local wisdom is carried out to instil local cultural values ​​and maintain the existence of these noble cultural values. This research method is qualitative research located at the Early Childhood Education Institute, namely RA (Raudhatul Athfal) Masyithoh 13 Sokaraja Lor. The observation technique was carried out to observe directly the learning process based on local wisdom. Collecting data using interview, observation and documentation techniques. The results of the study indicate that learning based on local wisdom is a form of innovation in integrating local wisdom of an area into early childhood education in developing aspects of the development of religious and moral values, emotional social, language, physical motoric, and art.